Characterization of Carrageenan Edible Film With Natural Antioxidant From Syzygium Cumini Leaf Extract (SCLE) - Reni Silvia Nasution (Elkawnie, 2022)
Abstract: Edible film have received considerable attention because of their advantages including their use as edible packaging material over synthetic films. This study aimed to characterize an edible film based on carrageenan and Syzygium cumini leaf extract (SCLE) as a natural antioxidant. The addition of SCLE was carried out with various concentrations of 0, 5, 10 and 15%. Characterization was carried out by measuring the physical properties, mechanical properties and antioxidant activities. The result showed that the presence of SCLE gave an increase in thickness and a decrease in solubility and water content compared to the edible film without the addition of SCLE. The addition of 5% SCLE resulted in a slight increase in tensile strength and a reduction in elongation at break. The edible films also showed an increase in antioxidant activity with the addition of SCLE where the highest antioxidant activity was at the addition of 15% SCLE. The incorporation of natural antioxidants in edible films can be a potential strategy to produce promising active packaging to extend product shelf life in the food packaging industry.Abstrak: Edible film telah mendapat banyak perhatian karena keuntungannya sebagai kemasan yang dapat dimakan  dibandingkan film sintetik. Tujuan dari penelitian ini adalah untuk mengkarakterisasi edible film berbasis karaginan dan ekstrak daun Syzygium cumini (SCLE) sebagai antioksidan alami. Penambahan SCLE dilakukan dengan variasi konsentrasi 0, 5, 10 dan 15%. Karakterisasi dilakukan dengan mengukur sifat fisika, sifat mekanik dan aktivitas antioksidannya. Hasil menunjukkan bahwa keberadaan SCLE memberikan peningkatan pada ketebalan dan penurunan pada kelarutan dan kadar air dibandingkan edibe film tanpa penambahan SCLE. Penambahan SCLE sebanyak 5% menghasilkan sedikit peningkatan pada kuat tarik dan pengurangan pada perpanjangan putus. Edible film juga menunjukkan peningkatan aktivitas antioksidan dengan penambahan SCLE dimana aktivitas antioksidan tertinggi pada penambahan 15% SCLE. Penggabungan antioksidan alami pada edible film dapat menjadi strategi potensial untuk menghasilkan kemasan aktif yang menjanjikan untuk memperpanjang umur simpan produk pada industri kemasan makanan.